Application of Teaching Material Science of SETS-Oriented to Increase the Ability of Science Literacy Junior High School Students - Ninda Yera Setyo Nainggolan; Bambang Subali; Sukiswo Supeni Edi (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2021)
Teaching materials are one part of learning tools that can help the teaching and learning process of both teachers and students. This study aims to determine the application of SETS-based science teaching materials to increase the scientific literacy skills of junior high school students. This study uses two classes as an experimental class. Treatment in the experimental class by giving SETS teaching materials with scientific literacy aspects and control classes using teaching materials used in daily teaching and learning activities. The learning process takes place at SMP N 01 Taman. The class is chosen as the control and experimental class with purposive sampling obtained from the mid-semester test scores. At the same time, the pretest-posttest method was used to determine whether the students' scientific literacy skills were good or not. The results of this study indicate that the application of SETS-based science materials with literacy aspects can significantly improve literacy skills. This can be seen from the calculation of N-Gain. Implementation of SETS-based science teaching materials can improve scientific literacy.